STRATEGI PELAKU USAHA KOPI GEROBAKAN DALAM MENERAPKAN PRINSIP KEWIRAUSAHAAN SYARIAH (DI WILAYAH: PASIR PENGARAIAN) - Ahmad, Aryan; Sawaluddin Sawaluddin; Muhammad Ilham; Rahmatika Ritonga (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the impact of mobile coffee cart businesses on the community and examine business development strategies as well as the application of Islamic economic principles in Pasir Pengaraian, Rokan Hulu Regency, Riau Province. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and literature review, involving mobile coffee cart business owners, consumers, and religious figures as informants. The findings indicate that mobile coffee cart businesses have a positive impact by improving access to coffee consumption, enhancing time efficiency, offering affordable prices, strengthening social interaction, and contributing to the local economy through job creation and new income sources. Business development strategies include maintaining consistent product quality, providing friendly and ethical services, setting fair and transparent prices, introducing menu innovations, utilizing social media for promotion, and applying Islamic entrepreneurial values. From an Islamic economic perspective, these practices generally reflect the principles of honesty, fairness, trustworthiness, and social responsibility, indicating that mobile coffee cart businesses function not only as community economic activities but also as a practical implementation of Islamic entrepreneurship with the potential to enhance community welfare and business sustainability.